2019
DOI: 10.14202/vetworld.2019.1608-1615
|View full text |Cite
|
Sign up to set email alerts
|

The effect of avocado seed powder (Persea americana Mill.) on the liver and kidney functions and meat quality of culled female quail (Coturnix coturnix japonica)

Abstract: Background and Aim: High temperatures have a detrimental effect on quail performance, even disrupting the immune system and function of the internal organs. This research aimed to investigate the effectiveness of avocado seed powder supplements on meat quality and the liver and kidney functions of culled female quails. Materials and Methods: A total of 100 six-month-old culled female quail were allotted to four dietary treatments, i.e., R0: Basal feed without avocado seed powder supplement and R1, R2, and R3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Literature on the effect of the use of ASF in rations on poultry meat pH and ruminants is still very limited. Previous research have reported that the addition of 6% avocado seed flour in basal ration can improve the quality of quail meat in terms of protein and cholesterol content [4]. Some literature also reported that the influence of the use of other feed ingredients containing flavonoids in the ration was related to meat pH.…”
Section: Results and Discussion Degree Of Acidity (Ph) Of Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on the effect of the use of ASF in rations on poultry meat pH and ruminants is still very limited. Previous research have reported that the addition of 6% avocado seed flour in basal ration can improve the quality of quail meat in terms of protein and cholesterol content [4]. Some literature also reported that the influence of the use of other feed ingredients containing flavonoids in the ration was related to meat pH.…”
Section: Results and Discussion Degree Of Acidity (Ph) Of Meatmentioning
confidence: 99%
“…Avocado seeds contain antioxidants [4] and are thought to have an effect on the physical quality of broiler chicken meat. The natural antioxidants are comprised of phenol derivatives, coumarins, sinamat hydroxy, tocopherols, diphenols, nonphenols, and ascorbic acid [5].…”
Section: Introductionmentioning
confidence: 99%
“…Avocado seed powder supplements on meat quality were determined Liver and kidney functions of culled female quails, serum glutamic oxaloacetic transaminase SGOT, and serum glutamic pyruvate transaminase SGPT were also determined. Avocado seed powder supplements improved meat quality as well as the liver and kidney functions of the culled female quail [71].…”
Section: Antioxidant Activity Of Avocado Seedmentioning
confidence: 98%
“…Then the blood samples were centrifuged at a speed of 3000 rpm for 5 minutes. The serum located at the top was separated to measure serum malondialdehyde and superoxide dismutase concentrations (Tugiyanti et al, 2019).…”
Section: Research Proceduresmentioning
confidence: 99%
“…The increase in blood glucose concentrations was caused by differences in the contents of flavonoids, saponins, and tannins in cassava leaf paste. Tugiyanti et al (2019) stated that flavonoids, saponins, and tannins could increase the acidic conditions in the pancreas and duodenum, thereby increasing the amylase enzyme activity in breaking down (Scholtz et al, 2009). Blood glucose in quails administered cassava leaf pastes at a dose of 15.87 mg/g (P3) decreased due to the accumulation of higher fiber content, and this fiber can lower blood glucose (Arif et al, 2018).…”
Section: Blood Chemistrymentioning
confidence: 99%